Synergistic effects of pain intensity and experiential avoidance in relation to anxiety symptoms and disorders among economically disadvantaged latinos in a community-based primary care setting. (May 2017) - Bakhshaie, Jafar; Kauffman, Brooke Y.; Viana, Andres G.; Garza, Monica; Ochoa-Perez, Melissa; Lemaire, Chad; Bogiaizian, Daniel; Robles, Zuzuky; Zvolensky, Michael J.
Highlights: Pain intensity and experiential avoidance were associated with anxiety psychopathology among Latinos in primary care. These associations remained significant after controlling for other contextual factors. Latinos with co-occurring pain and experiential avoidance evinced the greatest levels of anxiety psychopathology. Abstract: Latinos are subject to numerous health inequalities, including mental health disparity for anxiety and its disorders. In fact, there is strikingly little understanding of transdiagnostic risk factors for the onset and development of anxiety symptoms and disorders among Latinos. To build knowledge in this domain, the present investigation examined the interactive effects of experiential avoidance and pain intensity in relation to anxious arousal, social anxiety, and anxiety disorders among 361 Latino adults with annual incomes of less than $30, 000 (87.5% female; Mage  = 38.8, SD  = 11.4, and 98.5% used Spanish as their first language) who attended a community-based primary healthcare clinic. As hypothesized, the interaction between experiential avoidance and pain intensity was significantly related to anxious arousal, social anxiety, and a number of anxiety disorders over and above the effects of other factors. The form of the significant interactions indicated that participants reporting co-occurring higher levels of experiential avoidance and pain intensity evinced the greatest levels of anxious arousal, social anxiety, and anxiety disorders. These data provide novel empirical evidence suggesting that there is clinically-relevant interplay between experiential avoidance and pain intensity in regard to a relatively wide array of anxiety problems among Latinos in a primary care medical setting.